EASE OF DOING RESEARCH AND CONTRIBUTIONS TO RESEARCH OUTPUT AND IMPACT - A REGISTERED SYSTEMATIC REVIEW PROTOCOL - Joshua Owolabi (PEOPLE: International Journal of Social Sciences, 2026)
Objective: The objective of this review is to evaluate the influence of Ecosystem, Governance, and Resourcefulness and Resources factors - as defined by the Ease of Doing Research (EDR) framework - on research output and impact outcomes among researchers and research-active personnel in higher education institutions and research institutes globally. The review specifically examines evidence from both high-income (Global North) and low- and middle-income (Global South) country contexts to identify patterns of variation in how EDR pillar quality shapes research productivity, R&D contribution, and national development. Introduction: While extensive literature documents disparities in research output and R&D investment between high-income and low- and middle-income countries, individual studies have only examined discrete factors such as funding, brain drain, institutional culture, and governance in isolation. Also, no systematic review has synthesised this evidence within a unified, multi-pillar framework. The Ease of Doing Research (EDR) framework, which proposes three interconnected pillars - Ecosystem, Governance, and Resourcefulness and Resources - as the primary determinants of research productivity and impact, now provides the conceptual basis for a globally applicable synthesis, addressing a gap with significant implications for research policy, equity in scholarship, and the translation of research into national development. Inclusion Criteria: This review will include quantitative, qualitative, and mixed-methods studies examining Ecosystem, Governance, and Resourcefulness and Resources factors in relation to research output and impact among researchers and research-active personnel in higher education institutions and research institutes globally, published in English from 2000 to the present, across both Global North and Global South settings. Studies set exclusively in pre-university contexts, those without a research output focus, opinion pieces without primary data, and predatory or retracted publications will be excluded. Methods: Searches are conducted in April 2026 across PubMed/MEDLINE, Scopus, Web of Science, ERIC, and African Journals Online, with Google Scholar used supplementarily; searches were limited to English-language publications from 2000 to the present. Two independent reviewers will screen studies, assess methodological quality using design-appropriate standardised instruments, and extracted data, with disagreements resolved by consensus. A narrative synthesis will be conducted, organised by EDR pillar and Global North versus Global South comparator groupings, with certainty of evidence assessed considering risk of bias, consistency, directness, and precision. Systematic Review Registration Number: Protocol Registration number in PROSPERO - PROSPERO 2026 CRD420261381800